Development of multi-functional cotton fabrics with Ag/AgBr–TiO2 nanocomposite coating. (18th January 2016) - Rana, Masud; Hao, Bin; Mu, Lei; Chen, Lin; Ma, Peng-Cheng
Abstract: This paper reported the preparation of multi-functional cotton fabrics with Ag/AgBr–TiO2 nanocomposite coating, aiming at enhancing the technical value of fabrics using a simple spray coating process. Various techniques were employed to characterize the changes on the mechanical, surface and physical properties of fabrics before and after coating. The results showed that the introduction of nanocomposite coating onto cotton fabrics significantly enhanced their mechanical properties under both warp and weft directions, along with a rectified surface property from the hydrophilic to the hydrophobic. More interestingly, the developed fabrics exhibited excellent antibacterial, selective oil adsorption behavior from oil-water mixtures and UV blocking activities, thus significantly enhancing the value of cotton fabrics for various applications.